Patterns of ecosystem functioning as tool for biological regionalization: the case of the Mediterranean-desert-tropical transition of Baja California - P. Cazorla, Beatriz; P. Garcillán, Pedro; Cabello, Javier; Alcaraz-Segura, Domingo; Reyes, Andrés; Peñas, Julio (Mediterranean Botany, 2021)
Large-scale ecological variations across Earth have important consequences for biodiversity and, therefore, for biological conservation. Despite the widespread use of ecological maps in conservation schemes, they have been based mainly on structural and compositional features but scarcely on functional dimensions of life. Incorporating functional variables complements and improves the descriptions of regionalizations and offers a new understanding of biodiversity patterns. The development of remote sensing measurement allows for the description of the functional patterns of ecosystems through Ecosystem Functional Types (EFTs), opening new opportunities to analyze the geography of life. This article aims to examine the relationships between ecological regionalization based on components and structure and patterns of ecosystem functioning. As proof of case, we chose the Baja California peninsula, whose singularity has generated a rich variety of ecological and biogeographical interpretations, mainly based on ecosystem components and structure. We hypothesize that patterns in ecosystem functioning reflect ecoregionalization based on composition and structure features. We identified Ecosystem Functional Types (EFTs), from three descriptors of the seasonal curves of MODIS Enhanced Vegetation Index (EVI) from 2001 to 2017. We characterized each ecoregion in terms of ecosystem functioning and we carried out a correspondence analysis between the EFTs classification and the ecoregions. At a large scale, EFTs showed a pattern with three general regions from northwest to south, capturing the north-south transition of climatic regimes shown in the ecoregions map, from the northwestern Mediterranean area to the southern tropical zone, with a desert transition area between them. However, differences between the functional characterization and some ecoregions were detected in ecoregions identified as discrepancy areas between authors. In particular, some ecoregions considered Mediterranean showed a Desert character in its functioning, and others considered as Desert were Tropical functionally. EFTs remotely sensed measured at regional scales provide the basis for a more comprehensive regionalization of geographical patterns of life and, therefore, an improvement for future conservation purposes.